2013
DOI: 10.1002/bmb.20736
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an ABCA1 variant associated with type 2 diabetes mellitus susceptibility for biochemistry and genetic laboratory courses

Abstract: We selected diabetes mellitus for this laboratory exercise to provide students with an explicit model for scientific research concerning the association between the R230C polymorphism and susceptibility to type 2 diabetes mellitus, which is highly prevalent in the Mexican population. We used a collaborative project-based learning to engage students to direct their own learning process. Students worked in small groups with the same learning goal to research, organize data, and present seminars to experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…T2D and MetS are multifactorial problems that combine environmental and genetic factors (Alpizar Caballero, 2013). Several studies have shown genetic variants associated with metabolic disorders in different populations worldwide (Legorreta‐Herrera et al., 2013; Velazquez‐Roman et al., 2021; Villarreal‐Molina et al., 2012). Due to genetic diversity, it is crucial to perform genetic studies in less‐represented populations as well.…”
Section: Discussionmentioning
confidence: 99%
“…T2D and MetS are multifactorial problems that combine environmental and genetic factors (Alpizar Caballero, 2013). Several studies have shown genetic variants associated with metabolic disorders in different populations worldwide (Legorreta‐Herrera et al., 2013; Velazquez‐Roman et al., 2021; Villarreal‐Molina et al., 2012). Due to genetic diversity, it is crucial to perform genetic studies in less‐represented populations as well.…”
Section: Discussionmentioning
confidence: 99%
“…Several other undergraduate laboratory experiments have been published to genotype medically relevant loci, including variants involved in type 2 diabetes, susceptibility to cancer, , blood type, lactose intolerance, and color vision . However, the experiment reported herein combines several advantageous elements, including its use of noninvasive DNA samples, rather than blood, its determination of an easily measurable phenotype during the same exercise, and its focus on a topic of great relevance to students, with the added bonus that they can determine their own genotypes.…”
Section: Introductionmentioning
confidence: 99%